Pemberian KIE Dengan Pengetahuan Ibu Nifas Mengenai Infeksi Masa Nifas Di Dusun Kelapa Dua - Dewi Susanti; Elen Parengkuan (Jurnal Pengabmas Masyarakat Sehat, 2021)
The puerperium begins after the placenta is born and ends when the uterus organs return to their pre-pregnancy state. The puerperium lasts about 6 weeks or 40 days but will recover completely within 3 months. The puerperium or postpartum period is also called puerperium which comes from the Latin word "puer" which means baby and "parous "which means giving birth. Based on data obtained according to recording and reporting from districts/cities, the maternal mortality rate (MMR / MMR) in Maluku Province fluctuated from 2006 to 2010. However, it decreased from 369 per 100,000 live births in 2006 to 288 per 100,000 births. live in 2010.Keywords: KIE, Knowledge, puerperal infection